2012
DOI: 10.1039/c2jm31408h
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrochemical characterization of ordered mesoporous carbon-reduced graphene oxide nanocomposites

Abstract: Ordered mesoporous carbon-reduced graphene oxide (OMC-RGO) composites were prepared using a solvent evaporation induced self-assembly method. We proposed a novel theory called Hanger-Bridge theory to explain how mesoporous carbon prevents RGO from agglomerating, and the RGO enhances the conductivity of mesoporous carbon as well as helping to load more Pt particles. The as-prepared OMC-RGO composites were used as catalyst supports to deposit Pt nanoparticles and facilitate electrocatalytic reactions as well. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…The XRD pattern of OMC exhibits two broad diffractionp eaks at 2 q = 20-30a nd 40-508,w hich can be indexed to (002) and (101) diffractions of amorphous carbon, respectively. [45] After ex situ loading with SnO 2 NPs, all characteristicX RD peaks of SnO 2 /OMC indicatethe high purity of the SnO 2 with the tetragonal rutile structure (JCPDS no. .…”
Section: Resultsmentioning
confidence: 99%
“…The XRD pattern of OMC exhibits two broad diffractionp eaks at 2 q = 20-30a nd 40-508,w hich can be indexed to (002) and (101) diffractions of amorphous carbon, respectively. [45] After ex situ loading with SnO 2 NPs, all characteristicX RD peaks of SnO 2 /OMC indicatethe high purity of the SnO 2 with the tetragonal rutile structure (JCPDS no. .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, other forms of mesoporous carbon materials also have been prepared and applied to noble metal catalyst support. The Hanger‐Bridge Theory was proposed by He and co‐workers to explain the synthesized ordered mesoporous‐carbon‐reduced graphene oxide (OMC‐RGO) composites . The new theory indicated that the ordered mesoporous carbon could prevent RGO from agglomerating, while the RGO enhances the conductivity of mesoporous carbon as well as increasing the Pt loading.…”
Section: Applications In Fuel Cellsmentioning
confidence: 99%
“…Graphene with a two-dimensional honeycomb lattice structure is composed of carbon six-membered rings, which is the foundation of the structure of allotrope of fullerenes, carbon-nanotubes and graphite [7,8]. The synthesized graphene-based new composite has been demonstrated as a noteworthy example of potentially useful in many various applications, such as fuel cells [9], lithium ion batteries [10], biotechnology [11], supercapacitors [12], photocatalysis [13] and the electromagnetic wave absorbing material [14][15][16], etc. The graphene synthesized by chemical reduction of graphene oxide might be a potential candidate for microwave absorbing material by reason that reduced graphene oxide (RGO) cannot only promote the continuous state to the Fermi energy level transition, but also introduce the polarization relaxation caused by defects and polar functional groups [17].…”
Section: Introductionmentioning
confidence: 99%